The Improvement of the Achievement of Islamic Education Learning Materials in Abbasid Period by Using Jigsaw Type on the Students of SMP Negeri 2 Kubu - Sri Hidayati (International Journal of Multi Discipline Science, 2021)
This Classroom Action Research (CAR) is motivated by learning that has been carried out in class VIII A SMP Negeri 2 Kubu which is still carrying out the learning process of Islamic Religious Education with conventional methods of lectures and questions and answers, thus making students passive in learning carried out so that resulting in students being less involved in learning activities. One of the learning methods to overcome these learning difficulties is the Jigsaw method. The purpose of this Classroom Action Research (CAR) is to determine the extent of learning through the Jigsaw method in improving the learning achievement of class VIII A students at SMP Negeri 2 Kubu. The instruments used in this study were observation and test. Data were analyzed using descriptive percentages. This Classroom action research (CAR) is carried out in 2 cycles, from the results of the actions taken are proven to improve student learning achievement in Islamic Religious Education lessons on the material of the Growth of Science during the Abbasid Period by achieving the KKM standard of 75, from 73,09% in cycle l, can increase to 81.90% in cycle 2. The results of this action research indicate that learning Islamic Religious Education through the Jigsaw method is effective and can improve the learning achievement of class VIII A students at SMP Negeri 2 Kubu.